2021
DOI: 10.1155/2021/5533590
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Effect of Compaction Work and Defect on the Strength of Soil‐Rock Mixture Subgrade

Abstract: Soil-rock mixture is a common filling material for earth dam and subgrade. In this study, research concerned on the evolution law of engineering characteristics of soil-rock mixture under different factors and the effect of defect on subgrade strength, and geotechnical tests were carried out to analyze the influence of different factors on engineering characteristics of soil-rock mixture in the study, and the physical model was carried out to analyze the effect of different compaction works on the resilient mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It can be observed that the increasing trends for both the physical experiment and numerical simulation results at the same mixing degree index are highly consistent. Although the q/p values in the physical experiments are higher than those in the numerical simulations by approximately 0.6-0.8, the result is acceptable when the shape factor is taken into account [22][23][24][25][26]. This is because the physical experiments used real particles, whose shapes deviate from spherical particles, while the numerical simulations use ideal spherical particles.…”
Section: Specimen's Propertiesmentioning
confidence: 87%
See 2 more Smart Citations
“…It can be observed that the increasing trends for both the physical experiment and numerical simulation results at the same mixing degree index are highly consistent. Although the q/p values in the physical experiments are higher than those in the numerical simulations by approximately 0.6-0.8, the result is acceptable when the shape factor is taken into account [22][23][24][25][26]. This is because the physical experiments used real particles, whose shapes deviate from spherical particles, while the numerical simulations use ideal spherical particles.…”
Section: Specimen's Propertiesmentioning
confidence: 87%
“…(a) Several researchers have focused on the relationship between coarse particle content and shear strength of binary geotechnical mixtures [20][21][22]. The results show that when the coarse particles content of a binary geotechnical mixture is outside the range of 25-75%, the physical and mechanical properties of the binary geotechnical mixture are usually affected by only the fine or coarse particles.…”
Section: Index Of Mixing Degreementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the optimum moisture content of SRM is generally less than 15%, and gradually decreases with the increase of coarse content [33][34][35]. At the same time, considering the natural moisture content of the SSRM, each SSRM group was proportioned for five different moisture contents (6%, 8%, 10%, 12%, 14%) [24], thoroughly mixed, and blanked for 24 h to maintain consistent internal moisture content.…”
Section: Experimental Schemementioning
confidence: 99%
“…It is often used in conjunction with reinforced materials and is widely used in engineering elds. As a subgrade foundation and abutment foundation in highway and railway engineering [2,3], and in tra c construction, the soil-rock mixture can be reinforced to achieve the purpose of crack resistance of the pavement [4,5]. When replacing and lling the foundation, the soil-rock mixture of natural grading or arti cial grading is often used as replacement lling [6,7].…”
Section: Introductionmentioning
confidence: 99%